Mistress Masham's repose - White, Terence Hanbury, 1906-1964; Eichenberg, Fritz (New York : G. P. Putnam's Sons, 1946)
Ten-year-old Maria, an orphaned heiress mistreated by evil guardians, discovers the descendants of the Lilliputians living on an island on a lake in the grounds of her English mansion
Keywords: Orphans -- Fiction; Characters in literature -- Fiction; England -- Fiction